Bargaining over Royalties in the Shadow of Litigation - Fabian Griem; Roman Inderst (ZBW – Leibniz Information Centre for Economics, 2020)
We model negotiations over patent royalties in the shadow of litigation through a Nash-in-Nash approach, where outside options, triggered in case of disagreement, are derived from a subsequent game of litigation. The outcome of litigation depends both on "hard determinants", such as relative patent strength, and on "soft determinants", such as parties' efficacy in litigation or their (known) preparedness to disrupt negotiations in favor of litigation. Amongst other things, this has implications for the interpretation of observed royalties in empirical analysis.
Keywords: C71; D45; O34; 330; Royalties; Litigation; Nash-in-Nash